Multiple Ventricular Septal Defects: A New Strategy - Corno, Antonio F.; Kandakure, Pramod R.; Dhannapuneni, Ramana R.; Gladman, Gordon; Venugopal, Prem; Alphonso, Nelson (Frontiers in Pediatrics, 2013)
INTRODUCTION A multicenter prospective study was conducted to evaluate a new strategy for multiple Ventricular Septal Defects (VSDs). MATERIALS AND METHODS From 2004 to 2012 17 consecutive children (3 premature, 14 infants), mean age 3.2months (9 days to 9 months), mean body weight 4.2kg (3.1 to 6.1 kg), with multiple VSDs underwent Pulmonary Artery Banding (PAB) with an adjustable FloWatch-PAB. Associated cardiac anomalies included patent ductus arteriosus (9), aortic coarctation (2), hypoplastic aortic arch (2) and left isomerism (1). Five patients (5/17 =29.4%) required pre-operative mechanical ventilation, with a mean duration of 64 days (7 to 240 days) RESULTS There were no early or late deaths during a mean follow-up of 48 months (7 to 98 months), with either FloWatch removal or last observation as end-points. FloWatch-PAB adjustments were required in all patients: a mean of 4.8 times/patient (2 to 9) to tighten the PAB, and a mean of 1.1 times/patient (0 to 3) to release the PAB with the patient’s growth. After a mean interval of 29 months (8 to 69 months) 10/17 (59%) patients underwent reoperation: 7/10 PAB removal, with closure of a remaining peri-membranous VSD in 6 and Damus-Kaye-Stansel, bi-directional Glenn, and atrial septectomy in 1; 3/9 patients required only PAB removal. All muscular multiple VSDs had closed in all 10 patients. PA reconstruction was required in 1/10 patient. In 5/7 of the remaining patients with the PAB still in situ, all muscular VSDs had already closed. The only 2 patients with persistent muscular multiple VSDs are the 2 patients with the shortest follow-up. CONCLUSIONS This reproducible new strategy with an adjustable PAB simplifies the management of infants with multiple VSDs and provides the following advantages: a) good results (0% mortality), delayed surgery with a high incidence (15/17=88%) of spontaneous closure of multiple muscular VSDs, and facilitated closure of residual peri-membranous VSD at an older age and h